Designing rare disease care pathways in the Republic of Ireland: a co-operative model - A. J. Ward (Orphanet Journal of Rare Diseases, 2022)
Abstract Background Rare diseases (RDs) are often complex, serious, chronic and multi-systemic conditions, associated with physical, sensory and intellectual disability. Patients require follow-up management from multiple medical specialists and health and social care professionals involving a high level of integrated care, service coordination and specified care pathways. Methods and objectives This pilot study aimed to explore the best approach for developing national RD care pathways in the Irish healthcare system in the context of a lack of agreed methodology. Irish clinical specialists and patient/lived experience experts were asked to map existing practice against evidence-based clinical practice guidelines (CPGs) and best practice recommendations from the European Reference Networks (ERNs) to develop optimal care pathways. The study focused on the more prevalent, multisystemic rare conditions that require multidisciplinary care, services, supports and therapeutic interventions. Results 29 rare conditions were selected across 18 ERNs, for care pathway development. Multidisciplinary input from multiple specialisms was relevant for all pathways. A high level of engagement was experienced from clinical leads and patient organisations. CPGs were identified for 26 of the conditions. Nurse specialist, Psychology, Medical Social Work and Database Manager roles were deemed essential for all care pathways. Access to the therapeutic Health Service Professionals: Physiotherapy, Occupational Therapy, and Speech and Language Therapy were seen as key requirements for holistic care. Genetic counselling was highlighted as a core discipline in 27 pathways demonstrating the importance of access to Clinical Genetics services for many people with RDs. Conclusions This study proposes a methodology for Irish RD care pathway development, in collaboration with patient/service user advocates. Common RD patient needs and health care professional interventions across all pathways were identified. Key RD stakeholders have endorsed this national care pathway initiative. Future research focused on the implementation of such care pathways is a priority.